Inventory Recording Training at the Indonesian Pharmaceutical Interest Association in the Special Region of Yogyakarta - Ilham Galih Dini Hari; Endang Sri Utami (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Micro, small, and medium enterprises (MSMEs) play a very important role in economic growth in Indonesia. MSMEs are referred to as part of the national economy that is independent and has great potential in order to prosper the community. One type of MSME that is growing rapidly today is pharmacies. However, due to the lack of knowledge of partners in recording inventory, partners have difficulty recording inventory. Even though Inventory is a very important element in the Trading Business. This service is here to overcome this problem by providing socialization about inventory recording in accordance with the ESME SAK and creating an inventory recording program based on the Excel Application to make it easier for Partners to record inventory. The results of this service activity show positive results where after socialization partners can record inventory properly according to the current ESME SAK. Usaha mikro, kecil, dan menengah (UMKM) memainkan peran yang sangat penting dalam pertumbuhan ekonomi di Indonesia. UMKM disebut sebagai bagian dari perekonomian nasional yang mandiri dan memiliki potensi besar dalam rangka mensejahterakan masyarakat. Salah satu jenis UMKM yang berkembang pesat saat ini adalah apotek. Namun, karena kurangnya pengetahuan mitra dalam mencatat persediaan, mitra mengalami kesulitan dalam mencatat persediaan. Padahal Persediaan merupakan elemen yang sangat penting dalam usaha dagang. Pengabdian ini hadir untuk mengatasi permasalahan tersebut dengan memberikan sosialisasi tentang pencatatan persediaan sesuai dengan SAK EMKM dan membuat program pencatatan persediaan berbasis Aplikasi Excel untuk memudahkan Mitra dalam mencatat persediaan. Hasil dari kegiatan pengabdian ini menunjukkan hasil positif dimana setelah sosialisasi mitra dapat mencatat persediaan dengan baik sesuai SAK EMKM saat ini.